FOPID Controlled Shunt Active Filter in IEEE Thirty Bus System with Improved Dynamic Time Response - Sundaramoorthy Dhandayuthapani; K Anisha (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This paper aims on improving the dynamic time response of a Wind Energy Conversion System (WECS) connected to IEEE Thirty Bus System(TBS) using Permanent Magnet Synchronous Generator (PMSG) in closed loop controlled Active Power Filter with FOPID. The simulation results are presented to find the effect of shunt active filter using FOPID controller. Open Loop Thirty Bus System (OLTBS) with change in load is simulated. The simulation results with PI and FOPID Controller based SAF are compared and the corresponding time-domain parameters are presented. The results indicate that FOPID Controller system has better response than PI controlled system.